PENGARUH SUPERVISI KEPALA SEKOLAH TERHADAP KINERJA GURU - Maryani, Sri; Primasari, Dwi Ammelia Galuh (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The purpose of this study was to determine the effect of school principal supervision on teacher performance. This study used a survey method with a research population of principals and teachers at SDN 2 Gelumbang, Gelumbang District, Muara Enim Regency. The method used is the survey method. Data collection techniques using questionnaires with Likert scale and Proportional Random Sampling techniques. Processing data using simple linear regression and multiple linear regression to find out the effect together. The results showed that the supervision of principals had a positive effect on teacher performance at SDN 2 Gelumbang, Gelumbang District, Muara Enim Regency.